Drug delivery strategies for platinum-based chemotherapy - Browning, R; Reardon, P; Parhizkar, M; Pedley, B; Edirisinghe, M; Knowles, J; Stride, E (American Chemical Society, 2017)
Few chemotherapeutics have had such an impact on cancer management as cis-diamminedichloridoplatinum(II) (CDDP), also known as cisplatin. The first member of the platinum based drug family, CDDP’s potent toxicity in disrupting DNA replication has led to its widespread use in multi-drug therapies, with particular benefit in patients with testicular cancers. However, CDDP also produces significant side effects that limit the maximum systemic dose. Various strategies have been developed to address this challenge including encapsulation within micro- or nanocarriers and the use of external stimuli such as ultrasound to promote uptake and release. The aim of this article is to look at these strategies and recent scientific and clinical developments.